Hubungan Penguasaan Unsur-Unsur Kalimat dengan Penyusunan Kalimat Tunggal Bahasa Indonesia pada Siswa Kelas X - Siti Yuliana; Setyorini Dwi Agustini; Hamliyah Hamliyah (Universitas Muhammadiyah Jember, 2025)
This research aims to describe the ability to mastery sentence elements, to compose single sentences of Bahasa, and describe the relationship between elements sentence mastery and the ability to compose single sentences of Bahasa. The participant in this research is Xth Grader MA Al Misri. This research used descriptive with a correlational approach. In this research, four research stages were used, namely: 1) determining the population and sample, 2) data collection techniques, 3) research instruments, and 4) data analysis techniques. The result of this research based on the data analysis found that the participants’ mastery in sentence elements is in a good category with an average score is 72,55. The participants’ writing ability to compose single sentences in Bahasa is in a good category with an average score is 71,63. The calculated r was found 0,953 which was greater (>) than r table with a significant level of 5%, that is 0,423. Based on the interpretation result of interpretation guideline table, found that the calculated r (0,923) is categorized as a strong category. The result of calculation showed that the calculated t (17,68) is greater (>) than t table (2,085). The correlation result of this study showed that the significance level of two-party test is 5% and dk = n-2 = 20. The conclusion of this study is there is a positive and significance correlation between the sentence elements mastery and the ability to compose single sentences of Bahasa in Xth Grader MA Al Misri, Curahmalang, Rambipuji, Jember.